Acquired Epidermodysplasia Verruciformis Post-renal Transplant: A Case Report of Rare Manifestation of Immunosuppression - Neupane, Bidhan; Jwarchan, Jayanti; Adhikari, Bishnu Prasad; Kumar, Ajay; Sapkota, Surendra; Paudel, Subash; Oli, Ashmita (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Acquired epidermodysplasia verruciformis (EV) is a rare dermatologic disorder linked to increased susceptibility to specific HPV infections in immunosuppressed states. We report a 43-year-old renal transplant recipient on prolonged immunosuppressive therapy with tacrolimus, mycophenolate mofetil, and corticosteroids who developed multiple asymptomatic wart-like papules and plaques on extremities, hypopigmented pityriasis versicolor-like macules on the trunk, and seborrheic keratosis-like lesions on the face. Histopathology confirmed EV, showing acanthosis, hyperkeratosis, and keratinocytes with pale blue cytoplasm, perinuclear halos, and mild nuclear dysplastic changes. Due to malignancy risk in sun-exposed areas, strict sun protection and follow-up were advised. With acitretin and imiquimod unavailable, lesions were managed with intralesional measles, mumps, rubella (MMR) vaccine, and topical keratolytic, resulting in partial regression. This case highlights the need for early recognition, vigilant monitoring, and tailored management of EV in immunosuppressed patients, emphasizing further research to refine therapeutic strategies in resource-limited settings.